An analysis of pharmacy workforce capacity in Saudi Arabia - Almaghaslah, Dalia (Frontiers in Pharmacology, 2023)
Previous reports have highlighted the core issues with the intelligence of the national pharmacy workforce reliance on non-native pharmacists, despite the increasing supply of local pharmacy graduates; limited participation of female pharmacists in the workforce; and inadequate proportions of pharmacists in primary healthcare centres, resulting in pharmaceutical services being provided without a pharmacist's supervision.The current study used a retrospective cross-sectional design and data was collected from January to